2020
DOI: 10.5152/archealthscires.2020.577543
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Synthetic Oxytocin Given at Birth on Postpartum Period: Traditional Review

Abstract: The aim of the journal is to publish original articles, reviews, rare case report and letters to the editors of the highest scientific and clinical value in health sciences as physiotherapy and rehabilitation, health management, social work, nursing, midwifery, language and speech therapy, audiology, ergotherapy and gerontology. The target audience of the journal includes all health professionals who are members of the health team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The sample size was calculated using the volume of postpartum blood loss reported in the study by Mansy 5 . The minimum sample size was calculated at 80% power, a 5% significance level, and an expected effect size of 0.53 (Cohen's d), and it was found to be 44 in each group and 88 in total.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated using the volume of postpartum blood loss reported in the study by Mansy 5 . The minimum sample size was calculated at 80% power, a 5% significance level, and an expected effect size of 0.53 (Cohen's d), and it was found to be 44 in each group and 88 in total.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that breastfeeding difficulties may be experienced in neonates due to exposure of the developing fetal brain, the protective blood-brain barrier of which is not yet mature, to high amounts of oxytocin 5 . Gomes et al reported in their study that there is an association between intrapartum oxytocin dose and an increased risk of early cessation of breastfeeding among infants 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been stated that hyperbilirubinemia can be seen in the newborn, and suction problems may occur as a result of the effects on reflexes associated with sucking. 3,4,8 The World Health Organization does not recommend routine use of oxytocin to speed up delivery in the intrapartum care guide for positive delivery experience. 9 When the literature is examined, there are a few studies in the world about the use of oxytocin during labor.…”
mentioning
confidence: 99%